Strategi Pemasaran Digital dalam Pengembangan Bisnis UMKM - Deddy Junaedi; Mia Ananda; Yati Oktavia; Nur Isnin Wulandari; Nur Fadila (HATTA : Jurnal Pendidikan Ekonomi dan Ilmu Ekonomi, 2023)
In the rapidly developing digital era, technology provides opportunities and challenges for society, especially in the economic and business sectors. This study aims to review digital marketing strategies that can help the development of Micro, Small, and Medium Enterprises (MSMEs). Using qualitative research methods and literature studies, this study found that digital marketing allows MSMEs to expand market share, attract customers, and build closer relationships with consumers. Digital marketing also provides the competitive advantage and innovation needed in this era. However, MSME actors still face obstacles in understanding technology, budget, and adaptation to digital transformation. Therefore, it is important for MSMEs to conduct an in-depth analysis of business needs and challenges, and evaluate the performance of digitalization strategies to ensure business sustainability and growth.